Repealing Ireland's Eighth Amendment: Abortion rights and democracy today. (1st August 2020) - Drążkiewicz, Ela; Strong, Thomas; Scheper‐Hughes, Nancy; Turpin, Hugh; Saris, A Jamie; Mishtal, Joanna; Wulff, Helena; French, Brigittine; Garvey, Pauline; Miller, Daniel; Murphy, Fiona; Maguire, Louise; et al.
Abstract : In 2018, the Irish public voted to repeal the Eighth Amendment to the Irish Constitution, which since 1983 banned abortion in the country. While this was a watershed moment in Irish history, it was not unconnected to wider discussions now taking place around the world concerning gender, reproductive rights, the future of religion, Church–State relationships, democracy and social movements. With this Forum, we want to prompt some anthropological interpretations of Ireland's repeal of the Eighth Amendment as a matter concerning not only reproductive rights, but also questions of life and death, faith and shame, women and men, state power and individual liberty, and more. We also ask what this event might mean (if anything) for other societies dealing with similar issues?